Unsur Tambahan dalam Frase Adjektiva - Ary Setyadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The adjective phrase consists of two functional elements, namely the core function which is filled by the adjective word (nature / state); and elements of function attributes, which are filled by additional elements (words added / adverbs); so understanding the adjective phrases can be explained: a combination of two or more words that made up the word adjective as the core element / center, and word / additional elements (words added / adverb) as attributes. Based on the data, it turns out the presence of additional elements in the adjective phrase has not received special attention by some Indonesian experts; so interestingly researched. Implementation of the strategic research base three stages, namely: I. provision / collection of data, II. Classification and data analysis, and III. Preparation / report writing. Phase I, the data obtained at the data source, both oral and written sources by referring method and recording technique. Phase II based on the behavior of additional elements on its ability to join the word adjective (nature / circumstances) as attributes and are optional. The data analysis is based on the application of linguistic theory in the field of syntax with the application of the `direct elements' method with techniques: substitution, deletion, expansion, permutation, and phrases. In accordance with the objectives to be achieved, which includes: 1. kinds of additional elements, which finally can be found many additional elements. 2. distribution / provision of an additional element layout, which ultimately has three distribution: a. located in front, b. located at the back; and c. can be located in front or behind. 3. The power capability of additional elements, which can eventually be found in combination of two or more additional elements. Phase III is ended by being able to present a research / study report as the objective to be achieved.